2021
DOI: 10.5935/2595-0118.20210052
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorder in adults: retrospective study

Abstract: BACKGROUND AND OBJECTIVES:The temporomandibular disorder (TMD) comprises clinical signs and symptoms involving masticatory muscles, the temporomandibular joint (TMJ) and associated structures, does not affect all people equally, and all individuals are not equally susceptible to it. The aim of this study was to investigate signs and symptoms present in individuals with TMD. METHODS: Cross-sectional study with 471 individuals with TMD, 394 women and 77 men, based on data from clinical records, diagnostic exams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…It would be a confusing factor for our study if the female sex was a risk factor for TMD. However, although some authors 4,9,16 have found that the number of women seeking treatment for TMD is greater than the number of men, implying that females are more affected by the condition, this has been interpreted as a difference in attitude about oral health that reflects social, psychological, and behavioral discrepancies between the sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be a confusing factor for our study if the female sex was a risk factor for TMD. However, although some authors 4,9,16 have found that the number of women seeking treatment for TMD is greater than the number of men, implying that females are more affected by the condition, this has been interpreted as a difference in attitude about oral health that reflects social, psychological, and behavioral discrepancies between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The main signs and symptoms are pain in the muscles for mastication and/or TMA, sounds during condylar movement, and limitation or lack of coordinated jaw movement 3,4 . This pain triad appears together with mandibular disorder and articulatory sounds, as well as other clinical factors, including muscle and articulatory pain, palpation and during function, otalgia, tension headache, bruxism, trismus, limited mouth opening, pain in the cervical region, and static and dynamic abnormalities of the occlusal relationship 4,5 .…”
Section: Introductionmentioning
confidence: 99%